PENGARUH PERILAKU PEMIMPIN TERHADAP KEPUASAN KERJA DENGAN MEMPERTIMBANGKAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING PADA BURUH KONTAINER KOPERASI TKBM PELABUHAN AMBON - Kasmawati Ahmad (Universitas muhammadiyah malang, 2016)
The purpose of this research is to analyse the influence of leader behavior on the job satisfaction with locus of control as moderator variable. This research used primary and secondary data using the questionnaire, interview and documentation of 90 Ambon Port Employee Cooperation. Simple regression analysis, and MRA were employed to analyse the moderation effect. The result shows that leader behavior has a positive and significant effect on the job satisfaction. Locus of control does not moderating relationship between leader berhvaior and job satisfaction.